Personal Reminder System / Noorhasrina Mohd Isa and Nurul Aini Abd. Hamid - Mohd Isa, Noorhasrina; Abd. Hamid, Nurul Aini (2005)
A busy mind tends to forget events that are not of immediate concern. If we are fully involved in an activity, there is a possibility of forgetting other important engagements. To overcome this problem, we have come out with a device called ‘Personal Reminder System’. This device will help informs the person time to time, as it is pre-programmed. It may also be used simply as a sleep timer alarm. When the time for an event comes it will produce a beep sound together with blinking LEDs. It continues for a few minutes before going off automatically. This device is designed for 6V battery operation, to make the system portable. An external mains power supplies circuit also suitable for this device